2014
DOI: 10.1016/j.ijlp.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Pro-bullying attitudes among incarcerated juvenile delinquents: Antisocial behavior, psychopathic tendencies and violent crime

Abstract: The objective was to evaluate a new scale aimed at assessing antisocial attitudes, the Probullying Attitude Scale (PAS), on a group of 259 voluntarily-recruited male juvenile delinquents from a juvenile correctional institution in Arkhangelsk, North-western Russia.Exploratory factor analysis gave a two-factor solution: Factor 1 denoted Callous/Dominance and Factor 2 denoted Manipulativeness/Impulsiveness. Subjects with complete data on PAS and Childhood Psychopathy Scale (CPS) (n= 171) were divided into extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
(61 reference statements)
0
7
0
1
Order By: Relevance
“…A study on 170 pupils from Grade 7 to Grade 10 in the U.K. has shown that the mean score for support for victims ranged from 11 to 14, and the mean score for pro-bullying ranged from 7 to 8, indicating that most adolescents expressed a relatively high level of support for victims and anti-bullying attitudes [ 26 ]. However, attitudes in support of bullying were also reportedly present [ 24 , 28 ], considering the culture of manliness [ 24 ] and the misperception of social norms [ 23 ]. From an English primary school sample ( N = 326), Eslae and Smith (2000) found that although students were inclined to positive anti-bullying attitudes on the whole, 42% of students agreed that “most kids who bully do it for a reason,” and 38% of them agreed “I can understand how some children enjoy bullying” [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on 170 pupils from Grade 7 to Grade 10 in the U.K. has shown that the mean score for support for victims ranged from 11 to 14, and the mean score for pro-bullying ranged from 7 to 8, indicating that most adolescents expressed a relatively high level of support for victims and anti-bullying attitudes [ 26 ]. However, attitudes in support of bullying were also reportedly present [ 24 , 28 ], considering the culture of manliness [ 24 ] and the misperception of social norms [ 23 ]. From an English primary school sample ( N = 326), Eslae and Smith (2000) found that although students were inclined to positive anti-bullying attitudes on the whole, 42% of students agreed that “most kids who bully do it for a reason,” and 38% of them agreed “I can understand how some children enjoy bullying” [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research, for instance, indicates that social support is a protective factor (Konishi & Hymel, 2009) and bullying victimization (Cook, Williams, Guerra, Kim, & Sadek, 2010) and probullying attitudes (Golmaryami et al, 2016) risk factors for bullying perpetration. There is also evidence that low social support (Huebner & Betts, 2002), bullying victimization (Cullen, Unnever, Hartman, Turner, & Agnew, 2008), and probullying attitudes (Wiklund, Ruchkin, Koposov, & af Klinteberg, 2014) correlate with delinquency. Studies have identified parental knowledge of a child’s whereabouts and activities as a protective factor (Kerr & Stattin, 2000) and impulsivity/low self-control (Pratt & Cullen, 2000) and delinquent peer associations (Akers, 1998) as risk factors for delinquency.…”
mentioning
confidence: 99%
“…Despite a large body of literature suggesting the strong predictive power of psychopathy on dangerousnessviolent and aggressive behavior (Hecht, Berg, Lilienfeld, & Latzman, 2016;Reidy et al, 2015), violent criminal behavior (Dil & Kazmi, 2016;Wiklund, Ruchkin, Koposov, & Af Klinteberg, 2014), recidivism (Richards et al, 2016;Sturup, Karlberg, Fredriksson, Lihoff, & Kristiansson, 2016), and even violent recidivism (Richards et al, 2016;Sitney, Caldwell, & Caldwell, 2016)little is known about the role of psychopathic traits in IPV perpetration. Although traditional batterer typologies have suggested that psychopaths could belong to a specific batterer subtype-type 86 1 batterers, proposed by Gottman et al (1995), and Jacobson and Gottman (1998), or generally violent/antisocial (GVA) batterers, proposed by Holtzworth-Munroe and Stuart (1994)-further empirical studies testing these hypotheses are necessary.…”
mentioning
confidence: 99%